UPAYA MENINGKATKAN HASIL BELAJAR IPA PADA MATERI TEKANAN ZAT MELALUI PENERAPAN MODEL PROBEX - NURHASANAH NURHASANAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This classroom action research aims to improve science learning outcome on the basic theory of pressure in liquid for 8th grade students of MTs Al Hamid Jakarta for the academic year of 2019/2020 through the application of the PROBEX model. The research method used is classroom action research with four basic steps which are interrelated and sustainable, namely Planning, Action, Observation, Reflection which are designed in 2 cycles. The subject of this study is 8th grade students for the academic year of 2019/2020 at Madrasah Tsanawiyah Al Hamid Jakarta. The amount of research subject is 25 students. The result of the study concluded that the application of the PROBEX Model could improve science learning outcome on the main subject of Liquid Substance Pressure in 8th grade students of MTs Al Hamid East Jakarta in the academic year of 2019/2020, namely: it was only 32% before the completeness improvement, it reached 64% after the first cycle and it reached 92% after the implementation of the second cycle. ABSTRAKPenelitian tindakan kelas ini bertujuan untuk meningkatkan hasil belajar IPA pada teori pokok tekanan pada zat cair siswa kelas 8.A MTs Al Hamid Jakarta Tahun Pelajaran 2019/2020 melalui penerapan model PROBEX. Metode penelitian yang digunakan adalah penelitian tindakan kelas dengan empat tahap dasar yang saling terkait dan berkesinambungan, yaitu Planning (Rencana), Action (Tindakan), Observasi (pengamatan), Reflection (refleksi) yang dirancang dalam 2 siklus. Subjek penelitian ini adalah siswa kelas 8.A Tahun Pelajaran 2019/2020 yang berada di Madrasah Tsanawiyah Al Hamid Jakarta. Jumlah subyek penelitian 25 siswa. Hasil penelitian menyimpulkan bahwa Penerapan Model PROBEX dapat meningkatkan hasil belajar IPA pada materi pokok Tekanan Zat pada siswa kelas 8.A MTs Al Hamid Jakarta Timur Tahun Pelajaran 2019/2020, yaitu sebelum perbaikan ketuntasan hanya 32%, setelah siklus I mencapai 64% dan setelah pelaksanaan siklus II mencapai 92%.